Perceptions and acceptance of ‘belacan’ in Malaysian dishes - Leong, Quee Ling; Abdul Karim, Shahrim; Selamat, Jinap; Mohd Adzahan, Noranizan; Karim, Roselina; Jamaluddin, Rosita (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
This study aimed to analyze consumers’ perceptions and acceptance toward ‘belacan’. Results showed internal reliability of above 0.7 for sections analyzed. Factor analysis found two underlying factors in the section designed to examine consumers’ perceptions. The overall consumers’ perception had a positive and moderate correlation with their acceptance and was significant at .01. Results also showed that ‘belacan’ consumption level was relatively frequent and well accepted by all races in Malaysia. The findings of the study would be noteworthy to the fishery industry and the small and medium industry (SME) in Malaysia in meeting consumers’ needs.